IDENTIFICATION OF FINANCIAL RISKS IN THE ACCOUNTING INFORMATION SYSTEM: PROGNOSTIC CONTEXT - Галина Уманців; Олександр Коцупал; Алла Шаповалова; Олександр Задніпровський; Артем Хаванов (Фінансово-кредитна діяльність: проблеми теорії та практики)
The aim of the study is to highlight approaches to the identification and assessment of financial risks in the accounting information system in the context of forecasting the company's development. The author substantiates the position that forecasting the financial stability of an enterprise in the context of global challenges and martial law is quite difficult since these unfavourable factors form the circumstances that cause not only a reduction in the volume of active activity of an enterprise but also a potential complete shutdown and irreversible loss of property or resources. Force majeure circumstances are characterized by unpredictability and impossibility of forecasting, which complicates the process of analytical forecasting. The article concludes that in order to assess the impact on financial risk forecasting, it is necessary to carry out a number of procedures, including identification of certain types of risks, assessment of the range and reliability of information required to determine their level, and study of the impact of objective and subjective factors, influencing the level of enterprise risks, selection and use of methods for assessing the probability of occurrence of a risk event by certain types of risks, determination of the number of possible losses in the event of a risk event, establishing the maximum permissible level of risks for certain types of activities, taking into account the availability of risk management measures at the enterprise. The study concluded that after the start of the full-scale invasion, Ukrainian companies began to prepare financial forecasts more often. In the context of martial law, when the situation can change radically and within short periods of time, companies seek to adjust their expectations as often as possible in accordance with updated information.